Early-Onset and Preterm Preeclampsia After Bariatric Surgery [12K]. (May 2020) - Livergood, Mary Christine; Harrison, Rachel; Allen, Katherine; Lak, Kathleen; Cruz, Meredith
Abstract : INTRODUCTION: We sought to determine the rates of early-onset and preterm preeclampsia in women with a history of bariatric surgery compared to controls. METHODS: We performed a retrospective cohort study of 189 singleton pregnancies in women who had undergone a bariatric procedure prior to pregnancy and compared them to early pregnancy body mass index (BMI) and delivery date matched controls at a single center between 2005 and 2019. Early-onset and preterm preeclampsia were defined as preeclampsia requiring delivery prior to 34 weeks and 37 weeks, respectively. Pregnancy outcomes were compared using univariate and multivariate analysis. RESULTS: Of the 189 pregnant women with history of bariatric surgery, 5 (2.7%) had early-onset preeclampsia and 10 (5.3%) had preterm preeclampsia. Compared to early pregnancy BMI-matched controls, there was no difference between groups in the rates of early-onset preeclampsia (aOR 1.98, 95% CI 0.15-26.85). A subgroup analysis was performed on the rates of these disorders stratified by different types of bariatric surgery. Using gastric sleeve as the reference group, there were lower rates of early-onset preeclampsia and preterm preeclampsia in patients with a Roux-en-Y gastric bypass procedure (aOR 0.02 95% CI 0.00-0.95 and aOR 0.17 95% CI 0.03-0.99, respectively). CONCLUSION: Bariatric surgery was not associated with decreased rates of early-onset and preterm preeclampsia. In the subset of patients with a Roux-en-Y gastric bypass procedure, there were lower rates of preeclampsia prior to 34 and 37 weeks of gestation.